KAJIAN PERSEPSI KONSUMEN TERHADAP USAHA NASI KUNING SAROJA DI KOTA MANADO - Nur Hijriyana Jusuf; Leonardus R. Rengkung; Ribka M. Kumaat (Sam Ratulangi University, 2018)
This study aims to identify the consumer perception of â€œNasi Kuning Sarojaâ€ from aspects of price, taste, service, cleanliness, packaging and color. This study was conducted for 2 months by taking 70 respondents. The sampling process is conducted by purposive sampling. The results showed that the â€œNasi Kuning Sarojaâ€ has advantages in several aspects such as color, cleanliness, packaging, service and taste. While the price aspect is categorized as expensive.*lrr*.